2021
DOI: 10.1098/rsos.210025
|View full text |Cite
|
Sign up to set email alerts
|

Principled network extraction from images

Abstract: Images of natural systems may represent patterns of network-like structure, which could reveal important information about the topological properties of the underlying subject. However, the image itself does not automatically provide a formal definition of a network in terms of sets of nodes and edges. Instead, this information should be suitably extracted from the raw image data. Motivated by this, we present a principled model to extract network topologies from images that is scalable and efficient. We map t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…A promising approach is that of optimal transport theory. Recent studies [25,26] have shown that this theoretical formalism can be adapted to address multicommodity scenarios, generalizing well-established results for unicommodity models [27][28][29][30][31][32][33]. The works of Lonardi et al [25] and Bonifaci et al [26] focus on a theoretical characterization of the problem, drawing a formal connection between optimal transport and an equivalent dynamical system that is formulated in terms of physical quantities like conductivities and fluxes.…”
Section: Introductionmentioning
confidence: 81%
“…A promising approach is that of optimal transport theory. Recent studies [25,26] have shown that this theoretical formalism can be adapted to address multicommodity scenarios, generalizing well-established results for unicommodity models [27][28][29][30][31][32][33]. The works of Lonardi et al [25] and Bonifaci et al [26] focus on a theoretical characterization of the problem, drawing a formal connection between optimal transport and an equivalent dynamical system that is formulated in terms of physical quantities like conductivities and fluxes.…”
Section: Introductionmentioning
confidence: 81%
“…When fewer edges are used, hence we observe branched transportation, and the -Wasserstein cost coincides with a branched transport distance 25 , 53 . The idea of tuning to interpolate between various transportation regimes has been used in several works and engineering applications 27 , 54 59 .
Figure 2 Visualization of how impacts intra-community and inter-community edge weights.
…”
Section: β-Wasserstein Community Detection Algorithmmentioning
confidence: 99%
“…When β > 1 fewer edges are used, hence we observe branched transportation, and the β -Wasserstein cost coincides with a branched transport distance 21,36 . The idea of tuning β to interpolate between various transportation regimes has been used in several works and engineering applications 23,[37][38][39][40][41][42] .…”
Section: β -Wasserstein Community Detection Algorithmmentioning
confidence: 99%